Activation of mGluR4 promotes proliferation of rat neural progenitor cells while mediating activation of ERK1/2 signaling pathway - Duan, Z.; Zhang, X.; Zhu, G-X.; Gao, Y.; Xue, X. (Cellular and Molecular Biology, 2013)
Metabotropic glutamate receptors (mGluRs) influence the proliferation and differentiation of neural progenitor cells (NPCs) in the brain. They may play a major role in neurogenesis during embryonic development and in the adult brain. In this study, we investigated the expression of mGluR4 in NPCs and its possible role in the proliferation of rat embryonic NPCs in vitro, the expression of cyclin D1 and the activation of signaling pathways of mitogen-activated protein kinases (MAPKs). The results showed that mGluR4 protein was expressed in NPCs in vitro. mGluR4 selective agonist VU0155041 promoted the proliferation of NPCs by increasing cell activity, diameter of neurospheres and cell division. In addition, mGluR4 siRNA decreased the proliferation of NPCs. The protein expression of cyclin D1 increased with VU0155041 treatment and decreased after siRNA treatment. We also demonstrated that activation of ERK1/2 signaling pathways was involved in the proliferation of NPCs. VU0155041 increased phosphorylation of p-ERK1/2 levels, and mGluR4 siRNA decreased p-ERK1/2 levels. Furthermore, p-p38 expression was decreased by VU0155041 but was increased by mGluR4 siRNA. ERK1/2 inhibitor U0126 attenuated the increase of proliferation and cyclin D1 induced by VU0155041. These findings indicate that mGluR4 promotes the proliferation of rat NPCs and cyclin D1 expression through activation of ERK1/2 signaling pathways in vitro, suggesting that mGluR4 may play an important role in brain development. This study will help to develop a new potential therapeutic agent for brain injury and for the prevention of neurodegenerative disorders.